Is corporate governance risk valued? Evidence from directors' and officers' insurance - Boyer, M. Martin; Stern, Léa H. (Journal of Corporate Finance, 2012)
We find that common equity firms pay lower D&O insurance premiums than income trusts, an alternative and riskier ownership form. This result has wide-ranging implications for investors insofar as the information provided by D&O insurers provides investors with an unbiased signal of the firm's governance risk. The signal is unbiased because it comes from an entity (i.e. the insurer) that has a direct financial incentive to correctly assess an organization's governance risk, in contrast to other ad hoc governance measures and indices.